Melatonin Therapy Modulates Cerebral Metabolism and Enhances Remyelination by Increasing PDK4 in a Mouse Model of Multiple Sclerosis - Ghareghani, Majid; Scavo, Linda; Jand, Yahya; Farhadi, Naser; Sadeghi, Hossein; Ghanbari, Amir; Mondello, Stefania; Arnoult, Damien; Gharaghani, Sajjad; Zibara, Kazem (Frontiers in Pharmacology, 2019)
Metabolic disturbances have been implicated in demyelinating diseases including multiple sclerosis (MS). Melatonin, a naturally occurring hormone, has emerged as a potent neuroprotective candidate to reduce myelin loss and improve MS outcomes. In this study, we evaluated the effect of melatonin, at both physiological and pharmacological doses, on oligodendrocytes metabolism in an experimental autoimmune encephalomyelitis (EAE) mouse model of MS. Results showed that melatonin decreased the neurological disability scores and enhanced remyelination, significantly increasing myelin proteins levels including MBP, MOG and MOBP. In addition, melatonin administration attenuated inflammation as demonstrated by the reduction of pro-inflammatory cytokines (IL-1β and TNF-α) and the increase of anti-inflammatory cytokines (IL-4 and IL-10). Moreover, melatonin significantly increased brain concentrations of lactate, N-acetylaspartate (NAA), and 3-hydroxy-3-methylglutaryl-coenzyme-A reductase (HMGCR). Pyruvate dehydrogenase kinase-4 (PDK-4) mRNA and protein expression levels were also increased in melatonin treated mice, compared to untreated animals, whereas active and total pyruvate dehydrogenase complex (PDC) were significantly reduced. In summary, we have shown for the first time that melatonin inhibits PDC activity while increasing PDK4 levels. Our study suggests that melatonin may act to maintain cellular energetics metabolism, modulate neuroinflammation and enhance remyelination. Combining melatonin and PDK inhibitors may provide greater benefits for MS patients than the use of melatonin therapy alone.